UWB monopole antenna with enhanced gain and stable radiation pattern using gate like structures - Pandey G.K.; Singh H.S.; Bharti P.K.; Meshram M.K. (My University, 2025)
A new technique of employing gate like metallic structure on the ground plane to achieve enhanced gain and stable radiation pattern of an ultra-wideband (UWB) microstrip line fed planar monopole antenna is proposed. Two antennas with rectangular and semicircular gate like structures are designed having impedance bandwidth from 2 GHz to more than 11 GHz. The realized gain of the proposed antennas are found to be in the range of 3.98-7.44 dBi and 3.98-8.52 dBi for rectangular and semi-circular gate like structures, respectively. The proposed antennas also show nearly stable radiation patterns throughout the frequency band. © 2013 IEEE.